The Rational Paradigm in Islam: A Perspective on the Thought of Harun Nasution - Mubarok, Zulfi; Mustofa, M. Lutfi; Toriquddin, Toriquddin; Amalia, Amalia (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
The study of Harun Nasution's thought is very important to be studied more deeply because the study never stops being debated. The purpose of this paper is to understand 3 things: First, the paradigm of Harun Nasution's thinking. Second, internal and external factors that affect Harun Nasution's thinking. Third, the positive and negative implications of Harun Nasution's thoughts. The method used is library research with a qualitative approach based on Grounded theory, while data collection is by way of database search and literature review and analyzed with thematic analysis techniques. The results found are 3 things: First, Harun Nasution's paradigm of thought has 3 forms: (1) progressive rationality (2) Islamic renewal (3) Islamic rational theology.Second, internally influencing Harun Nasution's thinking there are 3 factors: (1) his knowledge in Islamic philosophy (2) his expertise in rationally oriented theology (3) his experience in moving the study of Islamic philosophy in Indonesia. As for externally, there are 3 factors that affect Harun Nasution's thinking: (1) the influence of Mu'tazilah's rationality (2) the inspiration of Muhammad Abduh (3) the integrity of education from other countries. Third, the positive implications of Harun Nasution's thinking on Muslims are 3 things (1) the development of philosophical knowledge. (2) the transformation of Islamic education towards openness, (3) the integrity of various disciplines. Meanwhile, the negative implications of Harun Nasution's thinking about Rational Islam on Muslims are 3 things: (1) controversy and disagreement of opinion (2) criticism of his thinking and learning which is considered inappropriate (3) his learning which is considered inappropriate. The conclusion that this paper shows that Harun Nasution's thinking has a significant complexity and influence on Muslims. An in-depth study of his thoughts needs to be carried out in order to understand its essence completely and contextually, as well as to answer various criticisms and questions that arise. [Kajian tentang pemikiran Harun Nasution sangat penting untuk dikaji lebih mendalam karena kajian tersebut tidak pernah berhenti untuk selalu diperdebatkan. Tujuan tulisan ini ingin memahami 3 hal: Pertama, paradigma pemikiran Harun Nasution. Kedua, faktor internal dan eksternal yang mempengaruhi pemikiran Harun Nasution. Ketiga, pemaknaan pemikiran positif dan negatif Harun Nasution. Metode yang digunakan adalah penelitian kepustakaan dengan pendekatan kualutatif berlandaskan teori Grounded theory, adapun pengumpulan data dengan cara penelusuran database dan observasi literatur serta dianalisis dengan teknik analisis tematik. Hasil yang ditemukan 3 hal: Pertama, paradigma pemikiran Harun Nasution ada 3 bentuk: (1) rasional progresif (2) pembaharuan Islam (3) teologi rasional Islam.Kedua, secara internal yang mempengaruhi pemikiran Harun Nasution ada 3 faktor : (1) keilmuannya dalam filsafat Islam (2) keahliannya dalam teologi yang berorientasi rasional (3) pengalamannya dalam menggerakan kajian filsafat Islam di Indonesia. Adapun secara eksternal yang mempengaruhi pemikiran Harun Nasution ada 3 faktor: (1) pengaruh rasionalitas Mu?tazilah (2) terispirasi dari Muhammad Abduh (3) integritas niali pendidikan dari negara lain. Ketiga, menanamkan pemikiran positif Harun Nasution terhadap umat Islam ada 3 hal (1) pengembangan ilmu yang filosofis. (2) transformasi pendidikan Islam keterbukaan (3) menuju pengintegrasian berbagai disiplin ilmu. Sedangkan, pemaknaan pemikiran negatif Harun Nasution tentang Islam Rasional terhadap umat Islam ada 3 hal: (1) kontroversi dan perselisihan pendapat (2) kritik atas pemikiran dan pembelajarannya yang dinilai tidak sesuai (3) pembelajarannya yang di nilai tidak sesuai. Kesimpulannya bahwa tulisan ini menunjukkan pemikiran Harun Nasution memiliki kompleksitas dan pengaruh yang signifikan terhadap umat Islam. Kajian mendalam tentang pemikiran beliau perlu terus dilakukan untuk memahami esensinya secara utuh dan kontekstual, serta untuk menjawab berbagai kritik dan pertanyaan yang muncul].